Sustainable Development and Protected Natural Areas: The Case of Tunkinsky National Park in Russia - Kirillov, Sergey; Vorobyevskaya, Elena; Slpenchuk, Mikhail; Zhuravlev, Viktor (European Journal of Sustainable Development, 2021)
The creation of rational nature management systems meets the needs of society and the necessary level of reproduction of natural resources and environmental protection. This is the main goal of the strategies for sustainable development of the regions. An integrated approach to assessing natural resource potential necessarily includes an economic assessment of the maximum possible number of environmental services. It forms the basis for territorial and sectoral planning. Protected natural areas have not only valuable biosphere resources, but also unique natural, historical and cultural opportunities for recreational activities. The territory of Tunkinsky National Park, located in the Republic of Buryatia in Russia, completely coincides with the borders of Tunkinsky administrative district of the Republic of Buryatia. Conflicts in the use of natural resources occur between the need to ensure the protection of nature and the development of economic activities. Using the example of Tunkinsky National Park, the role of a territory that is hardly affected by human economic activity, which provides ecologically important conditions for the life of society, is determined in monetary terms.